2003
DOI: 10.1016/s0899-3467(07)60067-6
|View full text |Cite
|
Sign up to set email alerts
|

Current standards for measuring spinal range of motion for impairment

Abstract: Measurement of spinal range of motion (ROM) along with strength, endurance, coordination, and sensation are among the essential determinants of musculoskeletal function. These measurements are important to the chiropractic physician concentrating in the fields of impairment rating, disability evaluation and independent medical examination (forensic examiner). An important initial step toward standardizing measurement of joint motion has been undertaken by the American Medical Association with their publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The authors of that review concluded that there was little evidence to support current measures of lumbar ROM. The poor results were mostly attributed to differences between the raters, reflected by the accuracy and consistency of manual palpation of bony landmarks, and the handling of the inclinometer heads along the subject’s spine [ 20 ]. Nonetheless, dual inclinometry is considered to be more valid tool than modified-modified Schobers (MMS) [ 21 ] because the measurement results are expressed in degrees, which correlate with the angular motion of lumbar flexion and extension [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of that review concluded that there was little evidence to support current measures of lumbar ROM. The poor results were mostly attributed to differences between the raters, reflected by the accuracy and consistency of manual palpation of bony landmarks, and the handling of the inclinometer heads along the subject’s spine [ 20 ]. Nonetheless, dual inclinometry is considered to be more valid tool than modified-modified Schobers (MMS) [ 21 ] because the measurement results are expressed in degrees, which correlate with the angular motion of lumbar flexion and extension [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term complications associated with aging affect spinal health and can cause significant functional impairments in activities of daily living [15,16]. Since spinal health and mobility are key determinants of whole body function, an increase in participation restrictions may result in a perceived quality of life change that is usually detrimental [23].…”
Section: Characteristics Of the Aging Spinementioning
confidence: 99%
“…However, biomechanically, only low levels of muscle contraction are needed to stabilize the spine during daily activities, further, individuals with chronic low back pain usually have increased levels of abdominal and lumbar muscle activity and the approach to increase the muscular demand during daily activities might be create a fear of movement, catastrophizing, muscle fatigue, more disability and pain [7]. Exercises focusing on spine mobility for individuals with low back pain have been Citation: Miranda historically prescribed after the American Medical Association and the American Academy of Orthopedic Surgeons suggested that measure spine mobility is a good approach to measure low back disability [8]. However, there are a few suggestions that the mobility of the lumbar spine seems to be poorly associated with movement functionality and low back disability [5], presenting poor or nonexistent relationship [9].…”
Section: Introductionmentioning
confidence: 99%